Circular siRNAs for Reducing Off-Target Effects and Enhancing Long-Term Gene Silencing in Cells and Mice - Liangliang Zhang; Duanwei Liang; Changmai Chen; Yuan Wang; Gubu Amu; Jiali Yang; Lijia Yu; Ivan J. Dmochowski; Xinjing Tang (Elsevier, 2018)
Circular non-coding RNAs are found to play important roles in biology but are still relatively unexplored as a structural motif for chemically regulating gene function. Here, we investigated whether small interfering RNA (siRNA) with a circular structure can circumvent off-target gene silencing, a problem often observed with standard linear duplex siRNA. In the present work, we, for the first time, synthesized a series of circular siRNAs by cyclizing two ends of a single-stranded RNA (sense or antisense strand) to construct circular siRNAs that were more resistant to enzymatic degradation. Gene silencing of GFP and luciferase was successfully achieved using these circular siRNAs with circular sense strand RNAs and their complementary linear antisense strand RNAs. The off-target effect of sense strand RNAs was evaluated and no cross off-target effects were observed. In addition, we successfully achieved longer gene-silencing efficiency in mice with circular siRNAs than with linear siRNAs. These results indicate the promise of circular siRNAs for overcoming off-target effects of siRNAs and enhancing the possible long-term effect of siRNA gene silencing in basic research and drug development.